2016
DOI: 10.1016/j.ijmedinf.2016.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Using mobile health technology to deliver decision support for self-monitoring after lung transplantation

Abstract: Background Lung transplant recipients (LTR) experience problems recognizing and reporting critical condition changes during their daily health self-monitoring. Pocket PATH®, a mobile health application, was designed to provide automatic feedback messages to LTR to guide decisions for detecting and reporting critical values of health indicators. Objectives To examine the degree to which LTR followed decision support messages to report recorded critical values, and to explore predictors of appropriately follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 62 publications
0
26
0
1
Order By: Relevance
“…The combination of high willingness and satisfaction rates provides a good prognosis for further studies. These results, however, may be limited by the low response rates in some studies and the apparent discordance in reported willingness and sustained utilization over time (Table ) .…”
Section: Posttransplant Phasementioning
confidence: 94%
See 1 more Smart Citation
“…The combination of high willingness and satisfaction rates provides a good prognosis for further studies. These results, however, may be limited by the low response rates in some studies and the apparent discordance in reported willingness and sustained utilization over time (Table ) .…”
Section: Posttransplant Phasementioning
confidence: 94%
“…Another well‐designed mHealth intervention, the Pocket PATH app, was able to demonstrate improved self‐monitoring (OR 5.11, 95% CI 2.95–8.87; p < 0.001) and adherence (OR 1.64, 95% CI 1.01–2.66; p = 0.046) in a large prospective randomized trial . Another study was able to demonstrate a 90% response rate to critical messages with the Pocket PATH, although there was no control group . Demonstrating the effect of multiple layers of mHealth interventions, Reese et al demonstrated significantly improved adherence with both customized reminders (78%) and customized reminders with notification to providers for adherence <90% (88%) compared with usual care (55%, p < 0.001 for each intervention group compared with controls) .…”
Section: Posttransplant Phasementioning
confidence: 99%
“…Chronically ill patients, however, are expected to use the app for years on a regular basis. It has been shown that gender, income, education, and regular use of technology, as well as the length of stay in a hospital predict the adherence to an eHealth tool [32]. Other studies confirm these findings with varying details [33–36].…”
Section: Mobile Applications (Apps)mentioning
confidence: 95%
“…Only 43% of centers met reporting thresholds for LKDs who donated in 2013, indicating that novel methods for collecting LKD follow-up data are needed. [10][11][12][13][14][15][16][17][18][19][20] However, mHealth technology has not yet been explored as a method for improving LKD follow-up, despite the well-documented challenges of collecting follow-up data. 9 Within the transplant community, mHealth technologies have been used to address numerous challenges in the field, including educating transplant recipients and candidates, improving adherence and self-management behaviors of recipients, helping patients on the waitlist find a living donor, and aiding in the screening and evaluation process of LKD candidates.…”
Section: Introductionmentioning
confidence: 99%
“…9 Within the transplant community, mHealth technologies have been used to address numerous challenges in the field, including educating transplant recipients and candidates, improving adherence and self-management behaviors of recipients, helping patients on the waitlist find a living donor, and aiding in the screening and evaluation process of LKD candidates. [10][11][12][13][14][15][16][17][18][19][20] However, mHealth technology has not yet been explored as a method for improving LKD follow-up, despite the well-documented challenges of collecting follow-up data. Improved follow-up data collection is needed to improve understanding of long-term risks associated with live donor nephrectomy, as existing analyses are limited by incomplete LKD follow-up data.…”
Section: Introductionmentioning
confidence: 99%